A new species of Maladera from Jordan (Coleoptera: Scarabaeidae: Sericini). Issue 4 (1st October 2016) - Ahrens, Dirk; Fabrizi, Silvia; Rößner, Eckehard
Abstract : A new Maladera species is described from Jordan: M. schnitteri sp. n. A key to the species of the subgenus Eusericula is given, and the habitus and genitalia are illustrated. http://www.zoobank.org/urn:lsid:zoobank.org:pub:D41D75B5-D700-4C2B-9058-04D14006C810